KOMPARASI METODE MOVING AVERAGE DAN TREND PROJECTION SEBAGAI ALAT UKUR PERENCANAAN PRODUKSI PADA UD. JAYA ABADI KABUPATEN PROBOLINGGO - Alvian Nuari; R. Hery Koeshardjono; M. Saiful Bahri (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2021)
The purpose of this research is to find out the comparison of forecasting calculations using the moving average and trend projection methods as a means measuring tool in production planning at UD. Jaya Abadi Probolinggo Regency. The type of research used is quantitative descriptive. Population and sample in this research is UD production data. Jaya Abadi Probolinggo Regerency from 2018 to March 2021. Data  analysis using the moving average and trend projection methods which aim to predict future production or the next period. The results showed that the value of  MAD (Mean Absolute Deviation)  and the MSE (Mean Square Error) moving average values are  higher than  the MAD  and the MSE trend projection, so the company you should use trend projection because when viewed  from the results of the comparision of  MAD and MSE, this method has a smaller error rate than the moving average method. So it can be concluded that the trend projection method can be used in planning bread production  at UD. Jaya Abadi Probolinggo Regency